2019
DOI: 10.7554/elife.46170
|View full text |Cite
|
Sign up to set email alerts
|

Trans-toxin ion-sensitivity of charybdotoxin-blocked potassium-channels reveals unbinding transitional states

Abstract: In silico and in vitro studies have made progress in understanding protein–protein complex formation; however, the molecular mechanisms for their dissociation are unclear. Protein–protein complexes, lasting from microseconds to years, often involve induced-fit, challenging computational or kinetic analysis. Charybdotoxin (CTX), a peptide from the Leiurus scorpion venom, blocks voltage-gated K+-channels in a unique example of binding/unbinding simplicity. CTX plugs the external mouth of K+-channels pore, stoppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Here, as in a prior report (11), we demonstrate that SAK1 toxins can use a second binding orientation in some channels so that an Arg confers voltage dependence rather than the nearby canonical Lys. Recently, high-speed atomic force microscopy was used to show that the affinity of the peptide AgTx2 increases in the KcsA pore over time, consistent with an induced fit binding model (35), and another group demonstrated that CTX can wobble between several bound conformations in Shaker channels so that the pore occluding Lys detaches sufficiently to allow cis-K + ions to enter the pore and alter blockade (36). Here, we also extend the utility of T-toxins to screening and quantifying the parameters of SAK1 toxin-channel interactions to facilitate the study of variants, particularly those with low affinity, in a manner that is amenable to the study of other peptides and membrane receptors.…”
Section: Two Sak1 Toxin-blocking Mechanismsmentioning
confidence: 78%
“…Here, as in a prior report (11), we demonstrate that SAK1 toxins can use a second binding orientation in some channels so that an Arg confers voltage dependence rather than the nearby canonical Lys. Recently, high-speed atomic force microscopy was used to show that the affinity of the peptide AgTx2 increases in the KcsA pore over time, consistent with an induced fit binding model (35), and another group demonstrated that CTX can wobble between several bound conformations in Shaker channels so that the pore occluding Lys detaches sufficiently to allow cis-K + ions to enter the pore and alter blockade (36). Here, we also extend the utility of T-toxins to screening and quantifying the parameters of SAK1 toxin-channel interactions to facilitate the study of variants, particularly those with low affinity, in a manner that is amenable to the study of other peptides and membrane receptors.…”
Section: Two Sak1 Toxin-blocking Mechanismsmentioning
confidence: 78%
“…One such non-trivial prediction offered by MD simulations of K + channel blockers relies on their different levels of interaction with the permeant ions. Classical pore blockers acting via a "molecular plug" mechanism directly compete with ions bound at the S1/S0 coordination sites, thus readily dissociate from their binding site when the external [K + ] is raised, or a strong depolarization is applied 27,28 . In contrast, Conk-S1, predicted to block ion conduction by triggering the collapse of the pore, thus avoiding any interaction with the permeant ions, was resilient to voltage-induced dissociation 20 .…”
Section: Experimental Validation Of Predictions Derived From the "Molecular Lid" Modelmentioning
confidence: 99%
“…One such non-trivial prediction offered by MD simulations of K + channel blockers rely on their different levels of interaction with the permeant ions. Classical pore blockers acting via a "molecular plug" mechanism directly compete with ions bound at the S1/S0 coordination sites, thus readily dissociate from their binding site when the external [K + ] is raised or a strong depolarization is applied 27,28 . In contrast, Conk-S1, predicted to block ion conduction by triggering collapse of the pore thus avoiding any interaction with the permeant ions, was resilient to voltage-induced dissociation 20 .…”
Section: Experimental Validation Of Predictions Derived From the "Molmentioning
confidence: 99%